Implementasi Program Corporate Social Responsibility Pt Astra Agro Lestari Pasangkayu Melalui Pilar Astra Hijau Dalam Penyediaan Air Bersih Di Kelurahan Martajaya - Elin; Esra Citra Togatorop; Amelia; Dinda Ayu Sintawati; Citra Lestari; Pratiwi; Fadilatunisa; Rachmad, S.Sos., M.Si (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the implementation of the Corporate Social Responsibility (CSR) program of PT Astra Agro Lestari through its subsidiary PT Pasangkayu under the Astra Green (Astra Hijau) pillar, specifically the clean water facility assistance program through water tank installations in Martajaya Urban Village, Pasangkayu District, Pasangkayu Regency, West Sulawesi. The research aims to describe the implementation process and identify supporting and inhibiting factors. A descriptive qualitative approach was employed through field observation and document review. The findings indicate that program implementation proceeded according to technical plans, supported by a pre-implementation needs assessment, synergy among stakeholders (company, village government, and community leaders), and positive community reception. Key supporting factors include stakeholder collaboration, sound technical planning, regulatory commitment under Law No. 40 of 2007, and high community acceptability. Inhibiting factors include geographic and seasonal challenges to water source availability, and the risk of low community participation in long-term maintenance. This program has had a positive impact on improved clean water access, enhanced sanitation conditions, and strengthened community ownership of the constructed facilities.